2013
DOI: 10.1111/trf.12048
|View full text |Cite
|
Sign up to set email alerts
|

Primary hemostatic capacity of whole blood: a comprehensive analysis of pathogen reduction and refrigeration effects over time

Abstract: BACKGROUND Whole blood (WB) has been used in combat since World War I as it is readily available and replaces every element of shed blood. Component therapy has become standard; however, recent military successes with WB resuscitation have revived the debate regarding wider WB use. Characterization of optimal WB storage is needed. We hypothesized that refrigeration preserves WB function and that a pathogen reduction technology (PRT) based on riboflavin and ultraviolet light has no deleterious effect over 21 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
187
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(210 citation statements)
references
References 52 publications
19
187
1
2
Order By: Relevance
“…Refrigerated PLTs are cleared over 2 to 3 days; thus, they certainly remain in circulation long enough to contribute to hemostasis during the crucial initial period after injury (10). Furthermore, recent data suggest that 4C-PLTs retain hemostatic function for at least 10 days when refrigerated (12,14). In the context of remote damage control resuscitation, whole blood or PLT units could be collected at support bases or forward locations and transported to remote sites in isothermal transport boxes (e.g., Golden Hour boxes) along with other blood products and medications.…”
Section: Cold Versus Room Temperature Storage Of Platelets For the Trmentioning
confidence: 99%
“…Refrigerated PLTs are cleared over 2 to 3 days; thus, they certainly remain in circulation long enough to contribute to hemostasis during the crucial initial period after injury (10). Furthermore, recent data suggest that 4C-PLTs retain hemostatic function for at least 10 days when refrigerated (12,14). In the context of remote damage control resuscitation, whole blood or PLT units could be collected at support bases or forward locations and transported to remote sites in isothermal transport boxes (e.g., Golden Hour boxes) along with other blood products and medications.…”
Section: Cold Versus Room Temperature Storage Of Platelets For the Trmentioning
confidence: 99%
“…The EXTEM MCF, used as a surrogate for platelet function, decreased over time. Though direct measurement of platelet function using aggregometry was not performed during the missions, the authors had previously reported on platelet aggregation [22]. Platelet function decreased significantly over time in CWB sample with a 50% loss from day 1 to day 5 with another 50% drop between days 5 and 10.…”
Section: Discussionmentioning
confidence: 99%
“…(41, 42) Refrigeration of CWB after pathogen reduction could ensure wide availability, hemostatic efficacy and enhanced safety in far forward settings, but must be weighed against its logistic burden. (43)…”
Section: Current Range Of Practicementioning
confidence: 99%
“…(43, 7880) The need for a practical way to provide hemostatically functional platelets to support RDCR suggests that platelet and whole blood refrigeration should be re-examined. The current standard of platelet storage, and by extension, limitation on whole blood use, is impractical for RDCR.…”
Section: Knowledge Gaps Where Future Research Endeavors Are Neededmentioning
confidence: 99%